Karakteristik Kuantitatif dan Kualitatif Hasil Persilangan Beberapa Ayam Lokal - Depison, Depison (Fakultas Peternakan Universitas Jambi, 2009)
This study was aimed to find out the results of the chicken cross Pelung Chicken with Lurik Chicken vs Komering and Lurik Chicken vs Komering Chicken. The experiment method was used in this study to reveal the data. Research variables were qualitative and quantitative characteristics. Quantitative characteristics included: the weight of eggs, hatching weight, fertility, body weight gain, and egg production. Qualitative characteristics included: hair color, comb shape, the color of the feet, skin and meal color. Data needed in this research obtained through measurements and observations of Pelung chicken, Lurik Chicken, Komering Chicken, the Crossbreed Chicken between Pelung Chicken vs Komering and Lurik Chicken. The data obtained were analyzed by way of summation, the percentage by X ± sd) (Steel and Torrie, 1993). Comparison of egg weight, fertility, hatching weight and body weightgain egg production, Crossbreed Chicken of Pelung Chicken vs Lurik Chicken and Lurik Chicken vs Komering was tested by t-test (Siegel, 1994). The result showed that : 1) The weight of the weight of hatching eggs and Pelung Chicken better than Lurik Chicken ad Komering Chicken in the weight andthe weight of hatching eggs. 2) In terms of weight, hatching weight and body weight gain, Crossbreed of Pelung Chicken vs Lurik Chiceken was better than a cross Pelung vs Komering and Lurik Chicken. 3) Lurik Chicken can be used as elder parents for the crossing program with other free-range chickenspecies for rising egg production.